2016
DOI: 10.1007/s40096-015-0172-7
|View full text |Cite
|
Sign up to set email alerts
|

Analytical studies for linear periodic systems of fractional order

Abstract: In this paper, new periodic fractional trigonometric functions with the period 2p a are presented. We have generalized the Floquet system to the fractional Floquet system. The fractional derivatives are described with the use of modified Riemann-Liouville derivative. Moreover, the stability analysis of fractional Floquet system is introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Rezazadeh et al recently examined the stability of Hilfer fractional differential equations system by using the properties of Mittag-Leffler functions [14]. In [15], the authors studied the stability for the fractional Floquet system and shown the fractional Floquet system is asymptotically stable if all multipliers have real parts between -1 and 1.…”
Section: Introductionmentioning
confidence: 99%
“…Rezazadeh et al recently examined the stability of Hilfer fractional differential equations system by using the properties of Mittag-Leffler functions [14]. In [15], the authors studied the stability for the fractional Floquet system and shown the fractional Floquet system is asymptotically stable if all multipliers have real parts between -1 and 1.…”
Section: Introductionmentioning
confidence: 99%
“…The following results give the stability analysis of such a system. [66,67] Theorem 1. A commensurate order system (39) is stable if the following condition is met:…”
Section: Stability Analysismentioning
confidence: 99%
“…The fractional derivative proposed by Hilfer yields Caputo (µ = 1) and Riemann Liouville derivative (µ = 0) as particular cases. Some recent works on fractional order Hilfer derivatives can be found in [13][14][15][16][17][18]. Perturbation techniques are powerful tools in nonlinear analysis for studying diverse aspects of the solution of nonlinear dynamical systems.…”
Section: Introductionmentioning
confidence: 99%